2020
DOI: 10.1155/2020/5269493
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Medical Treatment in Inflammatory Bowel Disease Patients from a Referral Center in Bahia-Brazil

Abstract: Background/Aims. Identify the degree of adherence to drug therapy in patients with inflammatory bowel diseases followed up at a referral center in Bahia-Brazil. Methods. Observational, analytical, and cross-sectional studies carried out from June/2017 to July/2018, with questionnaire application and medical record review at a referral center in inflammatory bowel diseases in Salvador, Bahia. The Morisky Green Levine Scale was applied to assess adherence. Mean, standard deviation, and frequency analyses were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
0
1
Order By: Relevance
“…As for the clinical status for UC, most of them had active disease at baseline, comparable to the proportion of patients with moderate to severe UC in Brazil [ 33 ]. Other studies in the country have found inverse results, with a higher proportion of patients with disease in remission, differing from the results presented here in [ 31 , 36 ]. It is noteworthy that the participants were assisted at a pharmaceutical service, while in other studies in Brazil, participants were interviewed during medical care assistance.…”
Section: Discussioncontrasting
confidence: 99%
“…As for the clinical status for UC, most of them had active disease at baseline, comparable to the proportion of patients with moderate to severe UC in Brazil [ 33 ]. Other studies in the country have found inverse results, with a higher proportion of patients with disease in remission, differing from the results presented here in [ 31 , 36 ]. It is noteworthy that the participants were assisted at a pharmaceutical service, while in other studies in Brazil, participants were interviewed during medical care assistance.…”
Section: Discussioncontrasting
confidence: 99%
“…As regard to residence, more than half of the studied sample was coming from urban areas. This finding is in agreement with (Andrade et al, 2020) who mentioned that more than three quarter of his study claimed to be from an urban area. This may be due to unavailable of specialized hospitals in rural areas and Westernization of lifestyle.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, highest prevalence of low adherence to pharmacological treatment of chronic diseases was associated with living in the Northeast and Midwest regions of the country and with worse self-perception of health (33) . Andrade et al (2020) assessed adherence to treatment among patients with the diagnosis of IBD in Bahia, Brazil, and most of them were classified as non-adherent (72.7%). Significant differences in adherence pattern were only found for gender among patients with UC (34) .…”
Section: Discussionmentioning
confidence: 99%
“…Andrade et al (2020) assessed adherence to treatment among patients with the diagnosis of IBD in Bahia, Brazil, and most of them were classified as non-adherent (72.7%). Significant differences in adherence pattern were only found for gender among patients with UC (34) .…”
Section: Discussionmentioning
confidence: 99%